Towards Universal Industrial Augmented Reality: Implementing a Modular IAR System to Support Assembly Processes - Detlef Gerhard; Matthias Neges; Jan Luca Siewert; Mario Wolf (Multimodal Technologies and Interaction, 2023)
While Industrial Augmented Reality (IAR) has many applications across the whole product lifecycle, most IAR applications today are custom-built for specific use-cases in practice. This contribution builds upon a scoping literature review of IAR data representations to present a modern, modular IAR architecture. The individual modules of the presented approach are either responsible for user interface and user interaction or for data processing. They are use-case neutral and independent of each other, while communicating through a strictly separated application layer. To demonstrate the architecture, this contribution presents an assembly process that is supported once with a pick-to-light system and once using in situ projections. Both are implemented on top of the novel architecture, allowing most of the work on the individual models to be reused. This IAR architecture, based on clearly separated modules with defined interfaces, particularly allows small companies with limited personnel resources to adapt IAR for their specific use-cases more easily than developing single-use applications from scratch.